THE COMPARISON OF JOHN CALVIN AND KARL BARTH ON THE DOCTRINE OF UNION WITH CHRIST - Jason Zhao (STTRII, 2018)
This article will continue to explore the influences of Calvin and Barth's different ontology on their distinct doctrine of union with Christ. After presenting Calvin's doctrine of union with Christ and Barth's teaching of participation in Christ, I will bring together the work of the previous study through comparison and evaluation. Although both Calvin and Barth adopt a Christocentric approach and similarly have a distinction between believers' objective and subjective union with Christ, their distinct ontological presuppositions, within their own philosophical and cultural contexts, drive Calvin to a theology of union with